2020
DOI: 10.1617/s11527-020-01549-x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of fly ash geopolymer binders to organic acids

Abstract: Fly ash geopolymers are a relatively new class of binders with the potential to reduce the CO2 emissions associated with Portland cement based construction materials. This paper reports on the organic acid resistance of fly ash geopolymers following exposure to acetic and lactic acid. Organic acids are prevalent in many circumstances including agriculture, production processes and waste management. These findings demonstrate that the surface of fly ash geopolymers had superior resistance to organic acids when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 87 publications
(114 reference statements)
4
24
0
Order By: Relevance
“…The biggest challenge in the former techniques was unaffordability, as they required high performance equipment and substantial energy. In the meantime, chemical binders (e.g., Portland cement (PC), fly ash, blast furnace slag, bentonite, and gypsum) were also used to improve the usability of the peat (Aiken et al, 2020;Hebib and Farrell, 2003;Paul and Hussain, 2020;Zulkifley et al, 2014). The PC was the most recommended binder among them, involving hydration processes to harden the peat (Kalantari, 2010;Paul and Hussain, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The biggest challenge in the former techniques was unaffordability, as they required high performance equipment and substantial energy. In the meantime, chemical binders (e.g., Portland cement (PC), fly ash, blast furnace slag, bentonite, and gypsum) were also used to improve the usability of the peat (Aiken et al, 2020;Hebib and Farrell, 2003;Paul and Hussain, 2020;Zulkifley et al, 2014). The PC was the most recommended binder among them, involving hydration processes to harden the peat (Kalantari, 2010;Paul and Hussain, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In future work, more advanced (numerical) modeling approaches are to be employed on the leaching results, in order to better separate the physical nature of the effective diffusion coefficient from the chemical binding isotherms, such as in [ 17 ]. Research so far has covered only empirical geopolymer tests on acid resistance [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], thus neglecting the fundamental chemical aspects behind it. Analogue mechanisms involved in dissolution of zeolites [ 35 ] demonstrate that decomposition of a network aluminosilicate in acid gradually shifts from initially congruent Si and Al dissolution to progressively preferential dissolution of Al, resulting in amorphous silica-rich gels, with gradually increasing Si/Al ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in high-calcium binders such as cement-based and high-calcium alkali-activated materials, acetic acid attack results in a high-porosity surface layer due to dissolution of the highly soluble acetate salts, complexation-enhanced solubility of Ca-rich (and Al-rich) phases and pH buffering characteristics. Aiken et al [ 6 ] also confirmed that fly ash-based geopolymers had a greater resistance to acetic and lactic acids than Portland cement, supported by smaller mass losses. This was ascribed to the higher stability of the geopolymer gel in organic acids compared to dissolvable Ca-rich cement systems, supported by a higher porosity in geopolymers that enables easier inward diffusion of the acid.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations